Developing Life Skills with Digital Comic Books to Improve Students' Critical Thinking Abilities in Science Subject - Karmila Bru Sebayang; Hasruddin Hasruddin; Sri Milfayetty (RIRAI Publisher, 2023)
This research aims to develop a life skills-based science material digital comic book teaching material product based on life skills that is feasible, practical and effective to use. This research uses development research (R&D) with a 4D model (Define, Design, Development, and Disseminate) with research subjects of 24 class IV students at SDN 068006 Medan. Data collection techniques use observation, tests, questionnaires and documentation. The results of the research produced feasibility with an average percentage of 91% in the